2021
DOI: 10.1101/2021.01.27.428373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abolished miR158 activity leads to 21-nucleotide tertiary phasiRNA biogenesis that targetsNHX2inArabidopsis thaliana

Abstract: Small RNAs including microRNAs (miRNAs) are short 20-24-nucleotide non-coding RNAs. They are key regulators of gene expression in plants and other organisms. Some small RNAs, mostly 22-nucleotide long trigger biogenesis of secondary small interfering RNAs (siRNAs). Those siRNAs having distinctive phased configuration are known as phased siRNAs (phasiRNAs) and act either in cis or trans enhancing silencing cascade. Here, we report natural variants of MIR158 having deletions or insertions led to negligible or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Further research found that the accumulation levels and the fractions of phasiRNAs were the highest in the wild type, as expected, but were also significantly higher in the conditionally fertile ocl4 compared to the ocl4 sterile samples, suggesting partial restoration of the phasiRNAs in the conditionally fertile plants ( Yadava et al., 2020 ). On the other hand, miR2118, miR390, miR472, miR3954, miR158, and miR482 could trigger the production of 21-nt phasiRNAs ( Fang et al., 2020 ; Tripathi et al., 2021 ). miR2275 is the unique miRNA known to trigger the production of 24-nt-dominated phasiRNAs, and all of these trigger events preferentially occurred in the tapetum and meiocytes.…”
Section: Phasirnas Play Important Regulatory Roles In Plant Male Ster...mentioning
confidence: 99%
“…Further research found that the accumulation levels and the fractions of phasiRNAs were the highest in the wild type, as expected, but were also significantly higher in the conditionally fertile ocl4 compared to the ocl4 sterile samples, suggesting partial restoration of the phasiRNAs in the conditionally fertile plants ( Yadava et al., 2020 ). On the other hand, miR2118, miR390, miR472, miR3954, miR158, and miR482 could trigger the production of 21-nt phasiRNAs ( Fang et al., 2020 ; Tripathi et al., 2021 ). miR2275 is the unique miRNA known to trigger the production of 24-nt-dominated phasiRNAs, and all of these trigger events preferentially occurred in the tapetum and meiocytes.…”
Section: Phasirnas Play Important Regulatory Roles In Plant Male Ster...mentioning
confidence: 99%